The praxis of interlanguage pragmatics instruction in an EFL context - Farashaiyan, Atieh; Kim, Hua Tan; Muthusamy, Paramasivam; Sahragard, Rahman (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research investigated the implementation of inter-language pragmatics instruction which is less explored in the research literature of instructional pragmatics in EFL contexts. Specifically, it examined the extent to which instructors of private EFL institutes implement interlanguage pragmatic instruction in their classrooms in Iran. A mixed-method research design was employed in this study. Two hundred and thirty eight instructors participated in this study to collect the questionnaire data and 67 classes were involved in the observation. Questionnaire and observation checklists made up the quantitative instruments for data collection while observation field notes provided the qualitative data. The quantitative data was subjected to descriptive statistics through the Statistical Package for Social Science (SPSS) version 21 software and the qualitative data was analyzed based on Martinez-Flor and Uso-Juan’s 6Rs instructional model. Findings from both the quantitative and qualitative data showed that Iranian EFL instructors rarely implemented and practiced the features of inter-language pragmatics in their classes in comparison with other language areas. The study suggests the inclusion of adequate pragmatic information not only in the instructors’ guidebooks but also in learners’ EFL textbooks and teacher training courses. The quality of EFL teaching can then be further enhanced at the higher learning institutions in EFL contexts.